Equi-biaxial fatigue behaviour of magnetorheological elastomers in magnetic fields. (March 2017) - Zhou, Yanfen; Johnson, Mark; Wen, Shipeng; Betts, Anthony; Jerrams, Stephen
The equi-biaxial fatigue behaviour of silicone-based magnetorheological elastomers in external magnetic fields was studied. Wöhler curves relating fatigue life to stress amplitude and dynamic stored energy for magnetorheological elastomers with a range of magnetic particle contents were derived. It was found that the fatigue life of magnetorheological elastomers in magnetic fields was higher than that without magnetic fields. Under constant stress amplitude conditions, the presence of magnetic fields resulted in longer times for the samples to undergo large deformations and thus complex modulus ( E *) decreased at a slower rate during the fatigue process, especially for low stress amplitudes. Magnetorheological elastomer samples tested in the presence of magnetic fields reached limiting values of E * at failure ranging from 1.28 to 1.44 MPa. The application of magnetic fields was found to have negligible influence on the damping loss factor of magnetorheological elastomers containing various volume fractions of carbonyl iron particles.